Brain‐Penetrant Triazolopyrimidine and Phenylpyrimidine Microtubule Stabilizers as Potential Leads to Treat Human African Trypanosomiasis. (7th August 2018) - Monti, Ludovica; Wang, Steven C; Oukoloff, Killian; Smith, Amos B.; Brunden, Kurt R.; Caffrey, Conor R.; Ballatore, Carlo
Abstract: In vitro whole‐organism screens of Trypanosoma brucei with representative examples of brain‐penetrant microtubule (MT)‐stabilizing agents identified lethal triazolopyrimidines and phenylpyrimidines with sub‐micromolar potency. In mammalian cells, these antiproliferative compounds disrupt MT integrity and decrease total tubulin levels. Their parasiticidal potency, combined with their generally favorable pharmacokinetic properties, which include oral bioavailability and brain penetration, suggest that these compounds are potential leads against human African trypanosomiasis. Abstract : A tip of the HAT : In vitro whole‐organism screens of Trypanosoma brucei with examples of different classes of small molecules known to modulate mammalian microtubule dynamics and structure resulted in the identification of a number of triazolopyrimidines and phenylpyrimidines with sub‐micromolar parasiticidal activity. Compounds of this type may be considered as potential leads against human African trypanosomiasis (HAT).